Review of Polishing the Chinese mirror - TAN, Sor-hoon (Institutional Knowledge at Singapore Management University, 2011)
Polishing the Chinese Mirror, edited by Marthe Chandler and Ronnie Littlejohn, is a collection celebrating the scholarship of Henry Rosemont, Jr. The list of c ontributors—including Roger Ames, Fred Dallmayr, Herbert Fingarette, P. J. Ivanhoe, Michael Nylan, Tu Wei-ming, and David Wong—reads like a veritable who’s who of Chinese and Comparative Philosophy and Religion. It contains nearly twenty essays addressing three areas that have benefited from Rosemont’s contributions: Chinese l inguistics, human rights, and East Asian traditions. Some but not all chapters engage Rose-mont’s works directly. This review focuses on discussions of his critique of Western human-rights doctrine and its underlying liberal conception of the self as autonomous individual. The few chapters examined in this brief review are not necessarily the best or most interesting, but simply those most relevant to two related strands selected from a very rich tapestry.